Post Traumatic dissection of vertebral artery:A case report .......... IJMTFM (2011) 1(1): 30-32 - Marjaei, A (International Journal of Medical Toxicology and Forensic Medicine, 2012)
This report presents a case of vertebral artery dissection (VAD), which was misdiagnosed as cerebrovascular accident (CVA) in initial examinations.In this case, a 33-year old woman, who was involved in a car accident, was referred to Khoy Legal Medicine Centre by traffic court two months after the accident.The patient was examined by the author, who was on an assignment at the centre.At this time, the patient had hemiparesthesia on the left side and was complaining of an increased appetite.CT angiography did not show right vertebral artery in vertebral foramen.The patient was diagnosed with right vertebral artery dissection accompanied by trauma based on the CT angiography results and the patient’s background of neck trauma resulting from the accident.